Sesquiterpenes: Natural Products That Decrease Cancer Growth - Modzelewska, A.; Sur, S.; Kumar, S.K.; Khan, S.R.
Despite recent advances in our understanding of the biological processes leading to the development of cancer, there is still a need for new and effective agents to help bring this disease under control. One of the oldest and most effective strategies for developing new chemotherapeutics is the isolation and evaluation of chemicals of natural origin. The importance of natural products for drug discovery has been impressive: One has to only look at the number of clinically active drugs that are used in cancer therapy to see how many are either natural products or are based on natural products. It is also apparent that materials from natural sources are excellent probes (indicators)for cellular targets that, when modulated, may have a deleterious effect upon the survival or proliferation of tumor cells. And the search goes on. Sesquiterpenes are a class of naturally occurring molecules that have demonstrated therapeutic potential in decreasing the progression of cancer. These molecules are 15-carbon isoprenoid compounds that are typically found in plants and marine life. Although this class of compounds has frequently provided encouraging leads for chemotherapeutics, they have not been evaluated as potential anticancer agents. In this review, we provide a current overview of sesquiterpenoids that have potential as anticancer agents.